MANHAJ PROF. DR. H. RAMLI ABDUL WAHID, MA DALAM BUKU:“FIKIH SUNNAH DALAM SOROTAN” - Muhammad Qomarullah (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2017)
The study of manahij al-muhaddisin is a mapping effort from various aspects of various scholars of hadith, both method, systematic, polarization that they make as reference for the people as the inheritance of the prophet. Well, it is that which makes the hadith experts from the times mutakaddimin and mutakhirin encouraged to get a track record of life and life of the Prophet. One of them is Prof. DR. H. Ramli Abdul Wahid, MA. He is a modern scholar who contributes to the track record of life-and the life of the prophet and as the first person to analyze the traditions contained in the book of Fiqh as-Sunnah by Sayyid Sabiq. The Book of Fiqh as-Sunna is quite popular among Fiqhi scholars, but through the cold hand it is the control and content of the hadith quoted by Sayyid Sabiq in his book is reanalyzed, thus becoming a new science reference for the modernist hadith. Prof. Dr. H. Ramli Abdul Wahid, Lc., MA is that he sees the book of Fiqh al-Sunnah is one of the rujkan used by scholars to be the source of determining the law, even the Majlis Ulama Indonesia (MUI) makes the book as one of the reference of the determination of the law